2023
DOI: 10.1002/cpdd.1240
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Recommendation Based on the Effects of Different Meal Types on Pexidartinib Pharmacokinetics in Healthy Subjects: Implementation of Model‐informed Drug Development Strategy

Abstract: Pexidartinib, an oral small molecule inhibitor of the colony-stimulating factor 1 receptor, is approved for treatment of adults with symptomatic tenosynovial giant cell tumor associated with severe morbidity or functional limitations and not amenable to improvement with surgery. The original dosing regimen is 400 mg of pexidartinib (2 × 200-mg capsules) twice daily, administered on an empty stomach at least 1 hour before or 2 hours after a meal or snack. Because pexidartinib is likely to be taken over an exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Food-effect studies conducted in healthy volunteers found that pexidartinib exposure increases with food consumption and approximately doubles when administered with an HFM over a dose range of 400-1800 mg; C max, AUC inf , and AUC from time 0 to the last quantifiable concentration all increased by approximately 100% with an HFM over this dose range. 11 Similarly, administration of 400-mg pexidartinib with an LFM, compared with the fasted state, resulted in a 56% increase in C max and a 59% increase in AUC inf . There was also a 71% increase in C max and a 66% increase in AUC inf for 200-mg pexidartinib administered with an LFM compared with 400-mg pexidartinib administered in a fasted state, dose normalized to 200 mg. 11 Using this information, it was estimated that the daily dose needed for administration of pexidartinib with an LFM is 500 mg to achieve equivalent exposure to an 800-mg daily dose administered on an empty stomach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Food-effect studies conducted in healthy volunteers found that pexidartinib exposure increases with food consumption and approximately doubles when administered with an HFM over a dose range of 400-1800 mg; C max, AUC inf , and AUC from time 0 to the last quantifiable concentration all increased by approximately 100% with an HFM over this dose range. 11 Similarly, administration of 400-mg pexidartinib with an LFM, compared with the fasted state, resulted in a 56% increase in C max and a 59% increase in AUC inf . There was also a 71% increase in C max and a 66% increase in AUC inf for 200-mg pexidartinib administered with an LFM compared with 400-mg pexidartinib administered in a fasted state, dose normalized to 200 mg. 11 Using this information, it was estimated that the daily dose needed for administration of pexidartinib with an LFM is 500 mg to achieve equivalent exposure to an 800-mg daily dose administered on an empty stomach.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, administration of 400-mg pexidartinib with an LFM, compared with the fasted state, resulted in a 56% increase in C max and a 59% increase in AUC inf . There was also a 71% increase in C max and a 66% increase in AUC inf for 200-mg pexidartinib administered with an LFM compared with 400-mg pexidartinib administered in a fasted state, dose normalized to 200 mg. 11 Using this information, it was estimated that the daily dose needed for administration of pexidartinib with an LFM is 500 mg to achieve equivalent exposure to an 800-mg daily dose administered on an empty stomach. This was confirmed using a model-informed bioequivalence study, in which clinical trial simulations showed that the use of 250-mg pexidartinib administered twice daily with an LFM would have an exposure similar to the original regimen of 400 mg administered twice daily on an empty stomach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations